Flexible Working Practices in the ICT Industry in Achieving Work-Life Balance - Ágota-Aliz Birtalan (Studia Universitatis Babes-Bolyai Sociologia, 2021)
Flexible labour practices became increasingly institutionalized and professionalized (Aroles, Mitev and de Vaujany, 2019). However, mechanisms and motivations behind these practices have remained often unexplored. This paper discusses the flexible labour practices among ICT professionals with regard to their spatial and temporal dimensions, with the aim to identify the key-factors that improve work-life balance and overall well-being. The qualitative research is based on in-depth face-to-face interviews with ICT knowledge workers, using Grounded Theory in generating new theoretical approaches that connect flexible labour practices with work-life balance. The study reveals, on the one hand, that particular and adapted flexible arrangements contributes to the reconciliation of the working life with the personal life; on the other hand, had led to the rise of knowledge workers with power and influence over their own intellectual capital, with a richness in personal choices.